Children's dominance in family vacation decision-making (FVDM): a multi-national analysis. Issue 3 (16th September 2021) - Chiang, Yu Chih; Su, Che-Jen; Liao, Hsin-Hsing; Chaudhary, Monica; Lan, Yi-Fang
Abstract : Purpose: This paper aims to explore adolescents' perceptions of child-parent dominance in family vacation decision-making (FVDM) by investigating child-parent relative influence (CPRI) and responsibility-sharing (RS) within the family in regard to 15 vacation issues. Design/methodology/approach: This paper adopts Davis and Rigaux's (1974) framework for identifying adolescents' perceptions of child-parent dominance across a set of subjects concerning FVDM, by inspecting the distribution of family decision roles across 25 nations. This study then segments the issues regarding family vacations and nations, judging by CPRI and RS within the family. In addition, this paper introduces Hofstede's cultural dimensions and diverse indices of development for each surveyed nation and compares their respective correlations with CPRI and RS at the national level. Findings: The results, derived from data collected in 25 countries or territories, illustrate a climate of a parent-dominant-to-autonomous style of FVDM for all decision issues and all nations. Overall, both information availability and economizing attribute of issues are related to the democratization of FVDM. The relationship between the child-parent role distribution and national clusters varied across issue clusters. In addition, the paper found the national effectiveness more effective than the cultural dimension in explaining the dispersal of CPRI-RS profiles. Originality/value: The data collected from 25 nations provide strong evidence for profiling child-parent dominance in FVDM. The data also serve as a basis for analyzing the role of sociocultural and ideological influences on child-parent dominance in FVDM, which was not established in previous research. Abstract : 子女在家庭渡假决策中的主导地位：多国分析研究 中文摘要 目的: 我们针对15个度假决策项目，调查青少年子女与父母的相对影响力（CPRI）和责任分担（RS），以探讨青少年在家庭渡假决策（FVDM）中相对于父母的支配地位的看法。 设计/方法/流程: 我们应用戴维斯（Davis）和里加（Rigaux）发表于1974 年的理论架构，调查25国中家庭决策角色的分配情况，从而确定青少年在家庭渡假决策相关决策项目中，子女-父母主导地位之看法。此外，我们根据"相对影响力"和"责任分担"来分别区隔决策项目与国家。我们也应用霍夫斯泰德的文化维度和多元社会发展指数，比较它们与"相对影响力"和"责任分担"的相关性。 结果: 从25个国家或地区收集的数据得出的结果表明，对于所有决策问题和所有国家来说，家庭渡假决策属于父母主导或自治风格的氛围。总体而言，资讯的可用性和问题的节约属性都与家庭渡假决策的民主化有关。子女-父母角色分布与国家集群之间的关系因决策项目集群而异。此外，我们发现，在解释"相对影响力-责任分担"侧像的分散方面，国家效能比文化维度更具影响力。 创意/价值: 我们从25个国家/地区收集的数据为分析家庭渡假决策中子女-父母的主导地位提供了有力的证据。并分析社会文化和意识形态影响对家庭渡假决策中子女-父母主导地位的基础，在现有的文献中尚未被建立。 Abstract : Predominancia de los hijos en la toma de decisiones de vacaciones familiares (FVDM): un análisis multi-nacional Propósito del articulo: Nosotros exploramos las percepciones adolescentes sobre la predominancia de padre e hijo en la toma de decisiones vacaciones en familiares (FVDM) mediante la investigación de la influencia relativa entre padres e hijos (CPRI) y la responsabilidad compartida (RS) dentro de la familia en relación con 15 temas de vacaciones. Diseño/ metodología/enfoque: Adaptamos el sistema de David and Rigaux para identificar las percepciones de adolescentes sobre el dominio padre e Hijo en un conjunto de temas relacionados con la FVDM, mediante la inspección de la distribución de los roles de decisión familiar a través de 25 países. Luego, segmentamos los problemas relacionados con las vacaciones familiares y naciones, juzgando por CPRI y RS con la familia. Además, presentamos las dimensiones culturales de Hofstede y los diversos índices de desarrollo para cada sociedad encuestada y comparamos sus respectivas correlaciones con CPRI y RS a nivel nacional. Resultados: Los resultados obtenidos de los casos recopilados en 25 países o territorios, ilustran un clima de estilo de FVDM de los padres en predominio autónomo para todos los temas de decisión y naciones. En general, tanto en los temas de disponibilidad de información como el atributo economizador están relacionadas con la democratización de la FVDM. La relación entre la distribución de roles de padres e hijos y los grupos nacionales vario entre los grupos temáticos. Además, encontramos que la eficacia nacional es más eficaz que la dimensión cultural para explicar la dispersión de los perfiles CPRI-RS. Originalidad/valor: Nuestros datos recopilados de 25 países proporcionan pruebas sólidas para perfilar el dominio de padres e hijos en la FVDM. Los datos también sirven como base para analizar el papel de la influencias socioculturales e ideológicas en el predominio de padres e hijos en la FVDM, que no se estableció en investigaciones anteriores.